Teacher - Šliogeris, Arvydas (Problemos, 1998)
The article is about Prof. E. Meškauskas as a person. The author of the article who was a disciple and younger colleague of prof. E. Meškauskas tells how prof. E. Meškauskas disclosed himself as a person brightly in the spontaneity of the Socratic dialoque liberating the mind of his disciple too.